The ecological effects of grazing by the White Rhino (Ceratotherium simum simum) at a landscape scale - Waldram, Matthew (Department of Biological Sciences, 2014)
In this thesis I generated hypotheses concerning the top down effect of grazing ungulates on grass communities and fire behavior from work done within grazing exclosures in Hluhluwe iMfolozi Park. White Rhino had a large influence in controlling grass biomass in Hluhluwe, a high rainfall mesic savanna. Other smaller species of grazers could not replicate the effect of White Rhino when their grazing was removed. In Umfolozi, a semi-arid savanna, other species of grazer could replace the effect of White Rhino grazing and exert a controlling influence on grass biomass. Hence the relative importance of different species of grazers changed along a rainfall gradient. When examined at a larger spatial scale I found that the removal of White Rhino led to a detectable change in grass biomass and in the grazing behavior of other species in the area of the removal. The effect that herbivores exerted on the grass layer also had consequences for the movement of fire through the landscape by reducing fuel loads. Burnt areas were larger and less patchy in areas from which White Rhino had been removed in comparison to control areas. This effect was larger in Hluhluwe but still significant in Umfolozi. I suggest that both fire and grazing are in competition for the same resource, grass, and that each results in conditions favorable to the recurrence of that event (fire or grazing). This allows the system to switch between mammal and fire dominated states. Rainfall shifts the balance of this competition and in mesic savannas White Rhino appear to be the only animal capable of competing successfully with fire. This work has application for the management of ecosystems that are influenced by top down control and for the maintenance of heterogeneity in mesic savannas.